Relationship between fruit growth and peduncle cross-sectional area in durian (durio zibethinus murray) - Ogawa, Kazuharu; Abdullah, Ahmad Makmom; Awang, Muhamad; Furukawa, Akio (Elsevier, 2007)
The relationship between fruit growth and peduncle cross-sectional area in the tropical tree Durio zibethinus Murray growing in an experimental field of Universiti Putra Malaysia (UPM), was examined. Fruit dry mass was allometrically related to the product of lateral and longitudinal fruit diameters by a power function, and the mass growth rate of the fruits was linearly related to the peduncle cross-sectional area. This linear relationship indicates that the specific fruit growth rate, defined as the fruit mass growth rate per unit cross-sectional area of peduncle, is constant. On the basis of previous findings of proportionality between the fruit growth rate and the rate of translocation of photosynthates into the fruit through the peduncle, it was concluded that fruit growth rate, translocation rate and peduncle cross-sectional area are proportional to each other.